Kashmir: towards demilitarisation - Raina, Pramathesh
The Security Forces have performed commendably in Jammu and Kashmir and have been singularly successful in containing insurgency to such levels that it has been possible to conduct free and fair elections and to restore life to a state of near-normalcy. Despite sterling results, reduction in troop levels on ground is not that visible for lack of a detailed study to ascertain the exact quantum and nature of troops that can be dispensed with given the current situation. Kashmir: Towards Demilitarisation is a seminal effort towards the understanding of the military nature of the Kashmir problem and working out a reasonable requirement of numbers and type of uniformed personnel to be responsible to maintain law and order and to combat the residual insurgency.
Keywords: Security and Foreign Affairs Sector; Civil War; Kashmir; Demilitarisation